Separation of Bio-oil by Hydrophilic Surfactants - Zhang, Mingming; Wu, Hongwei (American Chemical Society, 2018)
This study reports the effectiveness of bio-oil separation using several hydrophilic surfactants, including IGEPAL CO520, Tween 80, IGEPAL CO890, and sodium oleate, which have hydrophilic–lipophilic balance (HLB) values of 10, 15, 17, and 18, respectively. The results show that hydrophobic groups of surfactants (rather than HLB value) and surfactant concentration play significant roles in bio-oil separation. Permanent separation can be achieved at high surfactant loading levels (e.g., 5%) whereas a low surfactant concentration (e.g., 0.5%) leads to temporary separation. At 5% addition, IGEPAL surfactants (CO520 and CO890) require shorter separation time than Tween 80 and sodium oleate. Except the case with sodium oleate, the separation results in two layers (a clear layer and a dark layer). Compared to the dark layer, the clear layer has a lower carbon content and a higher oxygen content, leading to a lower aromaticity and a higher polarity. Water is more distributed in the clear layer, while aromatic compounds with fused rings are more concentrated in the dark layer. It is interesting to note that separation of bio-oil by sodium oleate results in an additional clear layer with distinct characteristics from the normal clear layers. This additional layer contains extractives in bio-oil and is at least composed of fatty acid esters.